Changes in total and percent distribution of joint power in distance runners over a competitive season - Arena, A. M.; Schemel, R.; Vargas-Blanchard, I. M.; Mokha, M. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to identify changes in joint power in distance runners over a competitive season. Thirteen cross-country runners (age, 19.8±2.2 yrs; height, 1.74±0.10 m; mass, 61.9±9.0 kg) from the same university team underwent 3D biomechanical gait analyses at the start and end of a seven-week competitive season. Total negative lower limb power did not change, p=0.641. Total positive power increased by 1.8 W/kg, but it was not significant, p=0.311. While negative joint power contributions shifted proximal to distal, these were not significant for ankle (p=0.404), knee (p=0.930), or hip (p=0.261). Positive joint power contributions shifted distal to proximal, the changes were not significant for the ankle (p=0.652), knee (p=0.776), or hip (p=0.156). Joint power contributions may potentially change over a competitive season and reflect fatigue or influence injury risk.